2009
DOI: 10.1007/s00011-009-0030-x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of mitogen-activated protein kinases and nuclear factor kappa B pathways in signaling COX-2 expression in chronic rhinosinusitis

Abstract: Upregulation of COX-2 expression suggested its role as a mediator in CRS. ERK and p38MAPK pathways were involved in signaling COX-2 through NF-kappaB pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
1
9
1
Order By: Relevance
“…These results suggest that intracellularly generated S1P is more effective in ameliorating LPS-induced IL-6 secretion than exogenously added sphingosine or S1P. S1PL Regulates LPS-Induced IL-6 Secretion through p38 MAPK and NF-kB Signal Transduction LPS stimulated NF-KB and ERK1/2 and p38 MAPK ( Figures E4A and E4B), confirming earlier studies in other cell types (35)(36)(37). Inhibition of p38 MAPK and NF-kB with Bay11-7082 and SB203580, but not ERK with PD98059, partly blocked LPSmediated IL-6 secretion in HLMVECs (Figures E4C and E4D).…”
Section: Role Of S1pl and Sphks In Lps-mediated Il-6 Secretion In Hlmsupporting
confidence: 87%
“…These results suggest that intracellularly generated S1P is more effective in ameliorating LPS-induced IL-6 secretion than exogenously added sphingosine or S1P. S1PL Regulates LPS-Induced IL-6 Secretion through p38 MAPK and NF-kB Signal Transduction LPS stimulated NF-KB and ERK1/2 and p38 MAPK ( Figures E4A and E4B), confirming earlier studies in other cell types (35)(36)(37). Inhibition of p38 MAPK and NF-kB with Bay11-7082 and SB203580, but not ERK with PD98059, partly blocked LPSmediated IL-6 secretion in HLMVECs (Figures E4C and E4D).…”
Section: Role Of S1pl and Sphks In Lps-mediated Il-6 Secretion In Hlmsupporting
confidence: 87%
“…A previous study showed that ECM-induced MMP-9 expression in RAW 264.7 macrophages is inhibited by celecoxib or siRNA-mediated reduction of COX-2 expression (22). Wang et al (39) demonstrated that COX-2-specific siRNA had no blocking effect on p38 MAPK, ERK, and NF-B pathway in LPS-induced human nasal epithelia (HNE) cells. After COX-2-specific siRNA was transfected into HNE cells, the LPS-induced COX-2 expression was blocked, and PGE 2 release was inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Kinases are known to play an important role in posttranscriptional control of inflammatory gene expression, T cell differentiation, and cell apoptosis. 7 Of the protein kinases highlighted in this analysis, individual studies have linked P38 MAP kinase 8,9 and ERK1/2 kinase 10 to sinusitis, whereas AKT, PKC, and JNK have not been studied specifically. Although there is considerable interest in using targeted kinase inhibitors to treat asthma and chronic obstructive pulmonary disease (COPD), 11,12 a similar strategy has not been widely proposed for sinusitis with polyps.…”
Section: Discussionmentioning
confidence: 99%